Adult Patient Education: A Readability Analysis of Hospital University Campus Bio-Medico's Patients Information Materials (PIMs) - Claudio Pensieri; Sabrina Saccoccia; Anna De Benedictis; Rossana Alloni (LED Edizioni Universitarie, 2022)
The UCBM's nurses and doctors have produced patients information material under the form of brochures that we delivered to patients in order to help them better understand their pathology, therapeutic path and procedure to which they will have to undergo. With the Covid-19, doctors necessarily spend less time with patients. This means that patients tend to (mis)inform themselves on internet. We analyzed the PIM's text readability with the Gulpease index. We submitted a qualitative questionnaire to 100 patients to evaluate the clarity of presentation and the communicative effectiveness and how much these allowed or not them to face their procedure with greater clarity and serenity. Brochures aroused interest in 77% of patients, where 87% declared that «The concepts are clear and I could understand them», 55% indicated that «The information is useful for understanding my condition». None of the them reach 40 pt. of the Gulpease index. Furthermore, the institutional font size was too small. Education of adult patient is a transversal area of pedagogy, medical clinic and communication. Experts from various fields (including patient associations) should collaborate to create informative materials that are useful for both patients and doctors/nurses.